Design, Synthesis and Anticancer Evaluation of New 1-allyl-4-oxo-6-(3,4,5- trimethoxyphenyl)-1,4-dihydropyrimidine-5-carbonitrile Bearing Pyrazole Moieties - Osman, Nermine A.; EL-Sayed, Nermine S.; Abdel Fattah, Hanan A.; Almalki, Ahmad J.; Kammoun, Ahmed K.; Ibrahim, Tarek S.; Alharbi, Abdulrahman S.; AL-Mahmoudy, Amany M. (Current Organic Synthesis, 2023)
Aim: pyrimidine and pyrazole have various biological and pharmaceutical applications such as antibacterial, antifungal, antileishmanial, anti-inflammatory, antitumor, and anti-cancer. Introduction: In this search, the goal is to prepare pyrimidine-pyrazoles and study their anticancer activity. Methods: 1-allyl-4-oxo-6-(3,4,5-trimethoxyphenyl)-1,4-dihydropyrimidine-5-carbonitrile bearing pyrazoles (4,6-8) have been synthesized. Firstly, the reaction of 1-allyl-2-(methylthio)-4-oxo-6- (3,4,5-trimethoxyphenyl)-1,4-dihydropyrimidine-5-carbonitrile (1) with chalcones 2a-b produced the intermediates 3a-b. The latter was reacted with hydrazine hydrate to give the targets 4a-b. On the other hand, hydrazinolysis of compound 1 yielded the hydrazino derivative 5 which upon reaction with chalcones 2c-i or 1,3-bicarbonyl compounds afforded the compounds 6-8. Finally, the new compounds were characterized by spectral data (IR, 1H NMR, 13C NMR) and elemental analysis. Moreover, they were evaluated for Panc-1, MCF-7, HT-29, A-549, and HPDE cell lines as anticancer activity. Results: All the tested compounds 3,4,6-8 showed IC50 values > 50 μg/mL against the HPDE cell line. Compounds 6a and 6e exhibited potent anticancer activity where the IC50 values in the range of 1.7- 1.9, 1.4-182, 1.75-1.8, and 1.5-1.9 μg/mL against Panc-1, MCF-7, HT-29, and A-549 cell lines. Conclusion: New pyrimidine-pyrazole derivatives were simply synthesized, in addition, some of them showed potential anticancer activity.
Keywords: anticancer